The Shariʻa history, ethics and law - Sajoo, Amyn B.; Institute of Ismaili Studies (London New York I.B. Tauris in association with the Institute of Ismaili Studies, 2018)
Why is the term shari'a - the mention of which conjures up images of a politicised religion in many parts of the world - understood in the ways that it is today? For Muslims and non-Muslims alike, much is read into this term, often with scant regard for its historical, cultural or theological underpinnings. This book offers an accessible account of the ideals and realities of the shari'a.
Introduction : multifaceted venture / Amyn B Sajoo -- Foundations /Khalid Abou El-Fadl -- Recovering the ethical : practices, politics, tradition / Ebrahim Moosa -- Sustaining and enhancing life / Karim H. Karim -- Spiritual refinement / Saʻdiyya Shaikh -- Women's equality / Ziba Mir-Hosseini -- Family law to finance / Mohamed M. Keshavjee and Raficq Abdulla -- Bioethics / Amyn B. Sajoo -- Legitimising authority : a muslim minority under Ottoman rule / Amaan Merali -- Democratisation and the Shariʻa : the Indonesian experience / Carool Kersten -- The Shariʻa in the Western landscape / Rex Ahdar and Nicholas Aroney -- 12. Secularism and the Shariʻa : lessons from an Ontario debate / Jennifer A. Selby.
Includes bibliographical references and index.
Keywords: Islamic law